Physician-Assisted Suicide in Dementia: Paradoxes, Pitfalls and the Need for Prudence - Rajkumar, Ravi Philip (Frontiers in Sociology, 2021)
There has been an increasing drive towards the legalization of physician-assisted suicide (PAS) in patients with dementia, particularly in patients with advanced disease and severe cognitive impairment. Advocacy for this position is often based on utilitarian philosophical principles, on appeals to the quality of life of the patient and their caregiver(s), or on economic constraints faced by caregivers as well as healthcare systems. In this paper, two lines of evidence against this position are presented. First, data on attitudes towards euthanasia for twenty-eight countries, obtained from the World Values Survey, is analyzed. An examination of this data shows that, paradoxically, positive attitudes towards this procedure are found in more economically advanced countries, and are strongly associated with specific cultural factors. Second, the literature on existing attitudes towards PAS in cases of dementia, along with ethical arguments for and against the practice, is reviewed and specific hazards for patients, caregivers and healthcare professionals are identified. On the basis of these findings, the author suggests that the practice of PAS in dementia is not one that can be widely or safely endorsed, on both cultural and ethical grounds. Instead, the medical field should work in collaboration with governmental, social welfare and patient advocacy services to ensure optimal physical, emotional and financial support to this group of patients and their caregivers.